Intensification of Vero cell adherence to microcarrier particles during cultivation in a wave bioreactor - Mazhed, Z. K.; Vasilenko, V. E.; Siniugina, A. A.; Kaa, K. V.; Motov, A. S.; Pokidova, K. O.; Ivin, Y. Y.; Piniaeva, A. N.; Khapchaev, Y. K.; Chernov, K. A.; Ishmukhametov, A. A. (Frontiers in Bioengineering and Biotechnology, 2025)
Vaccination is the most effective strategy for fighting viral diseases, with both live and inactivated vaccines remaining crucial despite advancements in subunit vaccine technologies. A key player in vaccine production is the Vero cell line, derived from the kidney cells of the African green monkey, which is essential for manufacturing vaccines against diseases like polio, rabies, yellow fever, and COVID-19. The efficiency of Vero cell cultivation directly impacts vaccine production, often utilizing bioreactors ranging from small (1–10 L) to large (up to several thousand liters). Wave-type bioreactors are commonly employed for initial cell propagation due to their simplicity. However, achieving uniform cell distribution on microcarriers in these systems poses challenges. This study aims to evaluate intermittent stirring during the early cultivation stages to enhance Vero cell distribution and growth, potentially improving overall cultivation efficiency.